Технология бурения геолого-разведочных скважин: справ. бурильщика / В. М. Винниченко, Н. Н. Максименко - Винниченко Владимир Митрофанович (Недра, 1988)
Экземпляры: КХ (20071219) / Инвентарный номер: 912429 / Цена: 0.50 / Сис.шифр: 622 / Авт.знак: В 48 / ГРНТИ: 52 / ББК: 3